Imported machines in the garden: the kyŏngun'gi (power tiller) and agricultural mechanization in South Korea. (2nd October 2017) - Choi, Hyungsub
ABSTRACT: The power tiller was central to the modernization of agricultural practices in East Asia during the latter part of the twentieth century. The small-scale, two-wheeled, walking-type power tiller was adapted from the European garden tractors by Japanese farmer-inventors in the 1920s, and then imported to South Korea in the early 1960s. This article traces the global technology circuit for power tillers, as well as their troublesome entry into the South Korean socioeconomic landscape in the 1960s and 1970s. Once the South Korean manufacturing industry for power tillers established itself, the agricultural machine was embroiled in a controversial political debate over landownership structures, which had profound implications for the very place of agriculture in modern South Korea. In the process of this extended debate, the social meaning of the power tiller itself went through significant change.